2011
DOI: 10.1111/j.1365-2214.2011.01216.x
|View full text |Cite
|
Sign up to set email alerts
|

Fairy tales: a compass for children's healthy development – a qualitative study in a Greek island

Abstract: The findings of this study emphasize the crucial role that storytelling plays in children's life and normal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…This nding is consistent with previous research indicating that children's books may play a role in the transmission of cultural values. (39,40) Previous research indicates that some cultural groups may not consider shared reading to be important in literacy promotion. A study of literacy promoting activities among Canadian parents reported that the majority of Canadian parents of ethnic Chinese origin tended not to prioritize shared reading as a literacy promotion activity when compared to Canadians of European ancestry.…”
Section: Resultsmentioning
confidence: 99%
“…This nding is consistent with previous research indicating that children's books may play a role in the transmission of cultural values. (39,40) Previous research indicates that some cultural groups may not consider shared reading to be important in literacy promotion. A study of literacy promoting activities among Canadian parents reported that the majority of Canadian parents of ethnic Chinese origin tended not to prioritize shared reading as a literacy promotion activity when compared to Canadians of European ancestry.…”
Section: Resultsmentioning
confidence: 99%
“…Data analysis was completed manually using content analysis (Graneheim and Lundman, 2004;Tsitsani et al, 2012). Initially, the first researcher reviewed the interview transcripts thoroughly and identified the meanings of each response.…”
Section: Discussionmentioning
confidence: 99%
“…(Κοζάκου-Τσιάρα, 1991) Καθώς η αξία του παραμυθιού είναι εξαιρετική, μακρόχρονη, διδακτική και η απήχηση του μεγάλη, αξιοποιήθηκε πλήρως από τις νηπιαγωγούς στις παραπάνω δράσεις, ενισχύοντας την θέληση και την προσπάθεια των μικρών παιδιών να συνδυάσουν λόγο, εικόνα και τεχνολογία. Τα παραμύθια «αποτελούν από τα πιο σημαντικά πολιτισμικά και κοινωνικά γεγονότα της ζωής τους, λειτουργώντας ως μέσα κοινωνικοποίησης και εκπολιτισμού» (Ράπτης, 2008. Tsitsani, Psyllidou, Batzios, Livas, Ouranos, & Cassimos, 2011.…”
Section: τελικά συμπεράσματαunclassified